Unlocking the Path to Academic Excellence: Unraveling the Impact of 480 Class Hours in Improving Reading Ability for Lecturers - Sadik, Andjarwati; Sahraeny, Sitti; Latief, Muhammad Ridha Anugrah (Utamax : Journal of Ultimate Research and Trends in Education, 2023)
This study seeks to explore the readers' ability experienced by adult learners who attended IELTS preparation courses at the Language Centre Hasanuddin University. It aims at measuring their progress through reading class. The respondents were 44 out of 50 lecturers from 18 different universities in the eastern part of Indonesia, both public and private, sponsored by the Directorate of Higher Education of the Republic of Indonesia. They attended 240 sessions which equaled 480 class hours for three months. The data were collected from the IELTS pre-test, progress-test, mid-test, and post-test. The progress test was given ten times during the preparation. By the end of the course, the participants sat for the real IELTS test administered by IALF Bali. They were also given a self-assessment questionnaire (20 questions) using a Likert scale ranging from "strongly agree to strongly disagree." Besides, the researchers also conducted direct observation as they were the teachers of Reading in their class. Based on the result of all instruments used in this research, the finding indicates that most of the respondents' reading ability is improving.